2001
DOI: 10.1021/jp0118017
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Heat of Argon Adsorption for the Evaluation of Relative Acid Strength of Some Sulfated Metal Oxides and H-type Zeolites

Abstract: The relative acid strength of sulfated SnO2, sulfated ZrO2, silica−alumina, H−Y, H−ZSM-5, and H-mordenite was estimated by the heat of Ar adsorption, calculated from a temperature dependence of amount of Ar adsorption around room temperature. These were 23.5, 23.6, and 13.8−16.5 kJ mol-1 for sulfated SnO2, sulfated ZrO2, and H-type zeolites, respectively. The data indicate that Ar is suitable for a probe molecule of acid sites on solid surface and that this technique is useful for evaluation of the acid streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Matsuhashi et al found that the relative acid strength of sulfated alumina [43], sulfated SnO 2 , sulfated ZrO 2 , silicaalumina, H-Y, H-ZSM-5, and H-mordenite [44] can be estimated by the heat of Ar adsorption, calculated from a temperature dependence of amount of Ar adsorption around room temperature. They proposed that for evaluation of the surface acidity, TPD of argon is a very useful method [45].…”
Section: Ar-tpdmentioning
confidence: 99%
“…Matsuhashi et al found that the relative acid strength of sulfated alumina [43], sulfated SnO 2 , sulfated ZrO 2 , silicaalumina, H-Y, H-ZSM-5, and H-mordenite [44] can be estimated by the heat of Ar adsorption, calculated from a temperature dependence of amount of Ar adsorption around room temperature. They proposed that for evaluation of the surface acidity, TPD of argon is a very useful method [45].…”
Section: Ar-tpdmentioning
confidence: 99%
“…The nitrogen quadrupole moment can interact with the dipole of hydroxyl groups on silica surfaces, and argon has been suggested as a probe for acid sites on silaceous materials (Matsuhashi et al 2001). The good agreement obtained, between the fitted value of the nitrogen monolayer capacity for the homotattic patch model, and the corresponding values obtained independently by SAXS, mercury porosimetry, and butane BET, suggests that the structural/geometric component of the model is probably correct.…”
Section: Discussionmentioning
confidence: 75%
“…Ar was found to be applicable as a probe for the temperatureprogrammed desorption. The acid strength can be estimated by the activation energy of Ar desorption from solid acids [19] or by the adsorption heat of Ar [20].…”
Section: Resultsmentioning
confidence: 99%